Analisis Kepuasan Pengguna Terhadap Aplikasi Sistem Informasi Kearsipan Pada Kantor Camat Medan Amplas Menggunakan Metode End User Computing Statisfaction(EUCS) - Siti Nurhalizah; Mesran (ADA Journal of Information System Research, 2023)
The Archives Information System is an application used to process and store letter data on the Medan Amplas Subdistrict Office website. Previously, the storage system that was being implemented had many shortcomings, therefore a website-based archiving application was created in the hope that it could help Medan Amplas District Head Office employees in processing and storing document archives. This application was created using a database programming language, and has several features, namely From the search data filter menu, From the Input archive data menu, From the add archive data menu, From the problem description menu, and From the print information menu.